Hydrogenation - Karamé, Iyad (IntechOpen, 2012)
The domain of catalytic hydrogenation continues to grow fast, reflecting the wide range of chemical applications that can be enhanced by the easy use of molecular hydrogen. The advances in characterization techniques and their application have improved our understanding of the catalytic processes and mechanisms occurring in both homogeneous and heterogeneous catalysis. The aim of this volume, although not exhaustive, is to provide a general overview of new progress of the hydrogenation reactions. This volume comprises a series of various contributions, as reviews or original articles, treating heterogeneously and homogeneously catalyzed hydrogenation reactions. It is composed of three parts: hydrogenation reactions in fine organic chemistry, hydrogenation reactions in environmental chemistry and renewable energy, and special topics in hydrogenation.